Exploration on the Influence of Artificial Intelligence Application in Mental Health on People’s Help-Seeking Behaviour and Mental Health Awareness - Qingdi Gu (Frontiers in Humanities and Social Sciences, 2026)
Artificial Intelligence (AI) is being used in the mental health field to develop generative AI chatbots and digital phenotyping; thus, the traditional psychological model has been challenged. Examine all kinds of changes in people's help-seeking behaviour and awareness of mental health due to AI applications. Although there are many mental illnesses around the world, most people are still unaware of them due to social stigma, high costs and a lack of health education. AI-led interventions provide users with an easy-to-access and private space for conversation with artificial intelligence to offer new kinds of mental health support. How interaction with AI affects the cognition of psychological problem recognition. Explainable AI (XAI) can help boost people's mental health literacy and provide a foundation for seeking professional mental health services, but there is also a risk of developing emotional dependence on Generative AI technology. Based on the latest empirical evidence for user self-disclosure, anticipated stigma and the construction of a 'digital therapeutic alliance', this study presents a dual-edged nature of AI. To maximise the health benefits for the public, AI should be used to construct an auxiliary triage system that supports human clinicians and enables appropriate referrals when needed.